Os negros, a educação e as políticas de ação afirmativa - Ana Lúcia Valente (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
This text seeks to further our understanding of the historical movement which underlies the implementation of policies of affirmative action for Negroes in the field of education considering this to be the condition for attending the interests and needs of this group, in the perspective of transformation. To this end, the text takes up reflections developed on other opportunities explaining ideas debated for years by scholars and militant Negroes and discussing the moments in which differences are transformed into a problem, when they are in fact distinctive and necessary marks of the human condition. Thereafter, we seek to evaluate the material and ideological conditions of present day capitalism, the process of ethnicisation of the work force and the dislocation of the debate from the cultural/ educational sphere promoted by international organisations.